Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis. Issue 5 (November 2021) - Huebner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif; Fasching, Peter A.; Beckmann, Matthias W.; Ruebner, Matthias; Burghaus, Stefanie
Highlights: High levels of ccfDNA can be isolated from plasma of endometriosis patients. Different methods for ccfDNA isolation can influence the output and integrity. Quantities of ccfDNA could be sufficient for further downstream applications. Abstract: Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method ( P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate ( P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.